Technology Research and Development for Environmental Management - With Specific Reference to Malaysia - B. Ghin Yeoh; Ahmad Zaharudin Idrus; K.S Ong (Universitas Gadjah Mada, 1988)
Technology Research and Development for Environmental Management - With Specific Reference to Malaysia